Leadership through theological education: Two case studies in South African history - G. A. Duncan (Verbum et Ecclesia, 2002)
The quality of visionary leadership requires serious attention in current South Africa, both because of its importance but also sometimes because of the lack of leadership in church and theological contexts. In the first section of this article, focus is placed on leadership in the Faculty of Theology (NG Kerk) at the University of Pretoria, and in the second section, on the leadership at the Lovedale Missionary Institution in the Eastern Cape. Finally, some comparisons and conditions are drawn.